Entrepreneurial intentions: personal and cultural variations. Issue 7 (27th October 2020) - Litzky, Barrie; Winkel, Doan; Hance, Jennifer; Howell, Ryan
Abstract : Purpose: The purpose of this study was to investigate the personal and contextual factors that influence entrepreneurial intention between two student populations from the United States and Portugal. Design/methodology/approach: The data were obtained through the Entrepreneurship Education Project, a large study that collected over 17, 000 responses from students in 70 countries. A subset of this data resulted in 3, 008 responses from students in the United States and 1, 026 respondents in Portugal. The model predicted that entrepreneurial intention would be influenced by entrepreneurial capital and entrepreneurial self-efficacy (ESE), and that the model results would be stronger in the US than in Portugal. Findings: The main effect hypotheses were supported while moderating effect hypotheses were not, although post hoc analysis revealed some interesting culturally relevant anecdotes. Research limitations/implications: This study contributes to the generalizability of previously established antecedents of entrepreneurial intention to two highly different cultural contexts – the United States and individuals from Portugal. The cross-sectional, correlational nature of the survey limits the findings to one point in time. Practical implications: Findings suggest that having the opportunity to start a business as part of entrepreneurship education may provide useful in not only enhancing ESE but also in entrepreneurial intentions. Programs might consider including starting a business, either a new venture, or as part of a corporate program as part of the degree requirement. It may be that starting a business will provide critical experience students need to choose entrepreneurship as a career. Originality/value: This research explored the similarities and differences in characteristics between students from a highly individualistic nation with low uncertainty avoidance (United States) and one that is more collectivist and less uncertainty avoidant (Portugal). Findings highlight the importance of entrepreneurial capital, ESE and the role that culture plays in students' entrepreneurial intentions.